Studies on the Effect of Oil and Surfactant on the Formation of Alginate-Based O/W Lidocaine Nanocarriers Using Nanoemulsion Template - Omar Sarheed; Manar Dibi; Kanteti V. R. N. S. Ramesh (MDPI AG, 2020)
The application of various nanocarrier systems was widely explored in the field of pharmaceuticals to achieve better drug encapsulation and delivery. The aim of this study was to encapsulate lidocaine in alginate-based o/w nanocarriers based on the type of oil (i.e., solid or liquid), using a nanoemulsion template prepared by ultrasound-assisted phase inversion temperature (PIT) approach. The nanoemulsion template was initially prepared by dissolving lidocaine in the oil phase and surfactant and alginate in the aqueous phase, and keeping the PIT at around 85 °C, accompanied by gradual water dilution at 25 °C, to initiate the formation of nanoparticles (o/w) with the aid of low frequency ultrasound. The composition and concentration of the oil phase had a major impact on the particle size and led to an increase in the size of the droplet. The lipids that showed a higher drug solubility also showed higher particle size. On the other hand, increasing the concentration of surfactant decreases the size of the droplet before the concentration of the surfactant exceeds the limit, after which the size of the particle increases due to the aggregates that could be produced from the excess surfactant. The method used produced nanoemulsions that maintained nano-sized droplets < 50 nm, over long-term storage. Our findings are important for the design of nanocarrier systems for the encapsulation of lipophilic molecules.